1969
DOI: 10.1287/opre.17.4.743
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor—Computational Results of an Integer Programming Algorithm

Abstract: Please scroll down for article-it is on subsequent pages With 12,500 members from nearly 90 countries, INFORMS is the largest international association of operations research (O.R.) and analytics professionals and students. INFORMS provides unique networking and learning opportunities for individual professionals, and organizations of all types and sizes, to better understand and use O.R. and analytics tools and methods to transform strategic visions and achieve better outcomes. For more information on INFORMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1969
1969
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Secondly, there were plenty of early attempts to implement cutting plane theory numerically nevertheless, c.f. Fleischmann (1970), Fiorot and Gondran (1969), Haldi and Isaacson (1965), Krolak (1969), Knuth (1961), Martin (1963), Miliotis (1978), Story andWagner (1963), Trauth Jr andWoolsey (1969), Wagner, Giglio, and Glaser (1964) and probably more. Most of the pertaining computational studies used the fractional cut (GP = ) or its "all-integer" variant (Glover, 1968;Gondran, 1973;Wilson, 1967;Young, 1968), whereas the stronger mixed-integer cut (GM # ) was studied to a lesser degree; probably because it makes a "mixed" integer program even more "mixed" as the surplus variable in (GM # ) is in general a flow variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, there were plenty of early attempts to implement cutting plane theory numerically nevertheless, c.f. Fleischmann (1970), Fiorot and Gondran (1969), Haldi and Isaacson (1965), Krolak (1969), Knuth (1961), Martin (1963), Miliotis (1978), Story andWagner (1963), Trauth Jr andWoolsey (1969), Wagner, Giglio, and Glaser (1964) and probably more. Most of the pertaining computational studies used the fractional cut (GP = ) or its "all-integer" variant (Glover, 1968;Gondran, 1973;Wilson, 1967;Young, 1968), whereas the stronger mixed-integer cut (GM # ) was studied to a lesser degree; probably because it makes a "mixed" integer program even more "mixed" as the surplus variable in (GM # ) is in general a flow variable.…”
Section: Discussionmentioning
confidence: 99%
“…(Krolak, 1969;Knuth, 1961;Story and Wagner, 1963) and Chapter 13 (written by R. Woolsey) in Salkin (1975). The only known exception to the rule was G. Martin's work (Martin, 1963) on set covering and traveling salesman problems of small to medium size; see also (Miliotis, 1978) where a discussion of implementational difficulties of Gomory's fractional cuts can be found.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there were plenty of early attempts to implement cutting plane theory numerically nevertheless, c.f. Fleischmann (1970), Fiorot and Gondran (1969), Haldi and Isaacson (1965), Krolak (1969), Knuth (1961), Martin (1963), Miliotis (1978), Story andWagner (1963), Trauth Jr andWoolsey (1969), Wagner, Giglio, and Glaser (1964) and probably more. Most of the pertaining computational studies used the fractional cut (GP = ) or its "all-integer" variant (Glover, 1968;Gondran, 1973;Wilson, 1967;Young, 1968), whereas the stronger mixed-integer cut (GM # ) was studied to a lesser degree; probably because it makes a "mixed" integer program even more "mixed" as the surplus variable in (GM # ) is in general a flow variable.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies reported in the early literature on the subject showed significant numerical success, indeed some reported outright disastrous results, c.f. (Krolak, 1969;Knuth, 1961;Story and Wagner, 1963) and Chapter 13 (written by R. Woolsey) in Salkin (1975). The only known exception to the rule was G. Martin's work (Martin, 1963) on set covering and traveling salesman problems of small to medium size; see also (Miliotis, 1978) where a discussion of implementational difficulties of Gomory's fractional cuts can be found.…”
Section: Discussionmentioning
confidence: 99%